Sistem Pembiayaan Pendidikan Dan Otonomi Daerah Dalam Meningkatkan Mutu Pendidikan - Sri Winarsih (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Regional autonomy is implemented since 2001 brought major changes in the management of education. That is why education is the most important component of financing in education. In the era of regional autonomy, the role of educator from kindergarten to high school are the responsibility of the region and the future of education depends on the ability of local governments to manage the education sector. But unfortunately the implementation of educational autonomy of the local government has not fully implemented due to budget constraints, there are at least six factors that influence it. In this paper the author will offer a range of alternative solutions that can be done either by the central government and local governments to resolve the issue. Keywords: autonomy, education, budget, local government.